1998
DOI: 10.1103/physrevb.58.10394
|View full text |Cite
|
Sign up to set email alerts
|

Band structure of BeTe: A combined experimental and theoretical study

Abstract: Using angle-resolved synchrotron-radiation photoemission spectroscopy we have determined the dispersion of the valence bands of BeTe(100) along ΓX, i.e. the [100] direction. The measurements are analyzed with the aid of a first-principles calculation of the BeTe bulk band structure as well as of the photoemission peaks as given by the momentum conserving bulk transitions. Taking the calculated unoccupied bands as final states of the photoemission process, we obtain an excellent agreement between experimental a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
44
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 29 publications
7
44
0
Order By: Relevance
“…Spectrum a was measured with a photon energy of 21.22 eV in normal emission (k k 0). Based on an estimate for the inner potential, V 0 10 AE 1 eV, which is in accordance with the values known for the (001) surfaces of II±VI semiconductors [17], the corresponding k c value is located at about 70% of the distance between the G-and the X-point. Spectrum b was also measured with He I but with an emission angle of 42…”
Section: Valence Band Offset At the Hgte/cdte(001) Interfacementioning
confidence: 99%
“…Spectrum a was measured with a photon energy of 21.22 eV in normal emission (k k 0). Based on an estimate for the inner potential, V 0 10 AE 1 eV, which is in accordance with the values known for the (001) surfaces of II±VI semiconductors [17], the corresponding k c value is located at about 70% of the distance between the G-and the X-point. Spectrum b was also measured with He I but with an emission angle of 42…”
Section: Valence Band Offset At the Hgte/cdte(001) Interfacementioning
confidence: 99%
“…Our results are in close agreement with the measurements compared to others. Interestingly, state-of-the-art GW calculations [11] also underestimate (2.6 eV) the bandgap for BeTe. It is worth noticing that our results clearly identify the difference in the X 3 c and X 1 c , the latter being higher by 0.44 eV.…”
mentioning
confidence: 95%
“…To our knowledge no such study is reported for BeTe or any other beryllium chalcogenide. The difficulty in growing single crystals along the principal crystallographic directions and the toxic nature could be the reason for the low number of experimental studies on these compounds [3,10,11]. However, the experimental Compton profile of ZnTe was reported [17] earlier using a 5Ci Am 241 source and was compared with the simple ionic model in the absence of any theoretical calculation.…”
mentioning
confidence: 99%
See 2 more Smart Citations